Estudo de viabilidade ambiental de sistemas fotovoltaicos conectados à rede, com base na análise de ciclo de vida - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
The Environmental Feasibility Study of Photovoltaic Systems Connected to the Network aims to analyze possible environmental impacts of this technology production processes. The justification is in the results obtained from this product Life Cycle Analysis, which showed significant environmental impacts according to the six categories examined - Depletion of Abiotic Resources, Climate Change, Depletion of the Ozone Layer, Human Toxicity, Acidification and Eutrophication. Data were obtained with the help of Software OpenLCA where the CML 2001 was chosen as a method of impact assessment and sustainability for a photovoltaic system installed in Switzerland composed of a photovoltaic panel, an inverter and a power 3kWp installation. The evaluation was made from the analysis of two models of panels, one (monocrystalline and multicrystalline). Both technologies have proved to be feasible from an environmental point of view. However, the choice of one or the other should be checked from other viewpoints, for multicristalina technology despite having less environmental impact, has lower efficiency compared to monocrystalline technology that even with higher efficiency is more expensive and pollutes more.
Keywords: Análise de Ciclo de Vida; Energia Fotovoltaica; Sustentabilidade; CNPQ::CIÊNCIAS EXATAS E DA TERRA; Energia Fotovoltaica, Sustentabilidade e Análise de Ciclo de vida.